The Influence of Instagram Social Media Marketing Communication Activities, Destination Image on Destination Brand Equity (Destination of Marine Tourism Ujung Kulon and Anak Krakatau, Banten) - Siti Susilawati (MediaKom : Jurnal Ilmiah Komunikasi, 2020)
Abstract: This study aims to determine the effect of Instagram social media marketing communication activities and destination image on destination brand equity. This is because competition in the tourist destination industry is so competitive and each tourist destination in Indonesia has different advantages and uniqueness. Therefore, to generate awareness, value, and loyalty of tourists requires marketing communication activities in the social media and create a distinctive image. Quantitative research methods, sampling techniques using simple random sampling and the research questionnaire was filled by 96 respondents. Quantitative data analysis uses multiple linear regression method. The results showed (1) Instagram social media marketing communication activities significantly influence destination brand equity. (2) destination image has a significant effect on destination brand equity. (3) Instagram social media marketing communication activities and destination image together have a significant effect on destination brand equity. The conclusion of destination image research gives the most powerful and significant effect on destination brand equity rather than Instagram's social media marketing communication activities.Keywords:social media marketing communication, destination image, brand equity, Ujung Kulon, Banten